Joan Mitchell - Roberts, Sarah ca. 20./21.Jh; Siegel, Katy 1966- (Yale University Press, 2020)
A sweeping retrospective exploring the oeuvre of an incandescent artist, revealing the ways that Mitchell expanded painting beyond Abstract Expressionism as well as the transatlantic contexts that shaped her0 Joan Mitchell (1925-1992) was fearless in her experimentation, creating works of unparalleled beauty, strength, and emotional intensity. This gorgeous book unfolds the story of an artistic master of the highest order, revealing the ways she expanded abstract painting and illuminating the transatlantic contexts that shaped her
Published to accompany the exhibition co-organized by The Baltimore Museum of Art 06.03.2022-14.08.2022 and the San Francisco Museum of Modern Art 04.09.2021-17.01.2022 [Ausstellungsdaten ermittelt]
Keywords: Mitchell, Joan -- 1925-1992; Ölmalerei; Abstrakte Malerei; Mitchell, Joan / 1925-1992 / Exhibitions; Abstract expressionism / United States; Painters / United States; Exhibition catalogs; Ausstellungskatalog -- Baltimore Museum of Art -- 06.03.22-14.08.2022 -- Baltimore; Ausstellungskatalog -- San Francisco Museum of Modern Art -- 04.09.21-17.01.2022 -- San Francisco